Karakteristik Mineralisasi Endapan Emas Epitermal Sulfidasi Rendah di Daerah Mekarbakti, Kecamatan Bungbulang, Kabupaten Garut, Provinsi Jawa Barat - Rangga Bintang Ardaraja; Eddy Winarno; Arifudin Idrus; Okki Verdiansyah; Satriadi Satriadi (Universitas Muslim Indonesia, 2022)
The southern mountains of western Java have been known to have large gold deposit potential. The Mekarbakti area, located in Garut regency, is known to have gold-bearing quartz veins, but the distribution and characteristics of these veins are not well recorded. The purpose of this study is to determine the geological conditions of the deposits and the characteristics of the epithermal deposits in the study area, in term of alteration, ore mineralization, vein texture, and ore geochemistry. Field work includes random sampling of veins from surface outcrops and cores. Laboratory analysis includes mineragraphic, geochemical analysis by means of Fire Assay Atomic Absorption Spectrophotometry (FA-AAS) and Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). The lithology of the Mekarbakti area is composed of volcanic rocks including andesite lava, andesite intrusion and pyroclastic rocks such as breccia and tuff. The mapping results show that the hydrothermal alteration that developed is divided into three zones of alteration type, namely the silicification zone (silica + - clay), the argillic zone (kaolinite + - smectite - illite) and the propylitic zone (chlorite - smectite - epidote - illite). Quartz texture is generally dominated by brecciated, colloform, comb, lattice bladed and cockade textures. The texture interpretation of the veins shows a crystalline quartz zone, which is enriched in base metals such as galena, sphalerite and chalcopyrite and a crustiform – colloform zone which usually contains gold and silver. Veins in the study area contain the elevated grades of 3.21 ppm Au and 75.5 ppm Ag.